Effect of oral clonidine in attenuating the haemodynamic responses to laryngodcopy and tracheal intubation in normotensive patient. - Joshi, Sumati (2001)
ABSTRACT: Laryngoscopy and tracheal intubation is often associated with undesirable variation in blood pressure and heat rate that is associated with an increase in morbidity and mortality especially in patients with hypertension, corenary artery disease and increase in intracranial pressure. Clonidine has been demonstrated to attenuate many of these detrimental effects when used as a premedicant. This randomized, double blind, placebo-controlled study was done to evaluate the effect of oral clonidine premedication (300 microgram) on the haemodynamic changes induced by laryngoscopy and tracheal intubation in seventy patients of either sexes, aged between 20 and 55 years of ASA I and II, scheduled for elective surgery under general anaesthesia. They received oral clonidine 300microgram and group B (n=35) who received placebo. Ninety minutes before the time of induction of anaesthesia, patients randomly received colonidine or a placebo in a double-blind fashion. Intravenous Pethidine 0.5 mg/kg was given and anaesthesia was induced with thiopental 5mg/kg IV followed by succinylcholine 1.5mg/kg IV to facilitate tracheal intubation. Heart rate and blood pressure both systolic and diastolic were measured noninvasively prior to induction (baseline values) and every minute for first ten minutes after intubation followed by every ten minutes till the end of surgery. There was no significant difference in demographic or baseline vital signs between two groups. The heart rate following laryngoscopy and tracheal intubation was significantly reduced (P<0.05) in clonidine treated group (105.29+-19.55 bpm) than in placebo group (120.26+-21.56 bpm). Compared to their baseline measurements (80.89+-6.14 bpm in clonidine group and 82.46+-7.03 bpm in placebo group), the heart rate following intubation was lower in clonidine group (30%) (Placebo-46%). However, iaryngoscopy and tracheal intubation significantly (P<0.000) increased systolic and diastolic blood pressures from their baselines at first three minutes in both the groups without any significant difference between the two. These increase perisisted throughout the study period albeit with decreasing magnitude. It is concluded that oral clonidine is effective in blunting the tachycardiac response to laryngoscopy and intubation but not the pressor response. Key Words: Clonidine, intubation, tachycardia, hypertension,